INVESTIGATION OF BUOYANCY FORCE AND LIFT OF NACA SERIES HYDROFOIL FOR WATER TURBINE - Azri Hamim Ab. Adzis , Mohd Azamuddin Mokhlis (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Hydropower is an economically viable source of renewable energy. The water turbine is one of the methods to generate hydropower. Hydrofoil creates lift force as when water flows through the hydrofoil it will exert an upward force on the foil. Lift force generates the kinetic energy of the water turbine and the kinetic energy is transformed into mechanical energy. This project focused on the investigation of buoyancy force and lift of NACA series hydrofoil for water turbine applications. The main problem of normal hydrofoils is when it approached the water surface the lift and drag force reduced and the velocity at which cavitation first emerged on the hydrofoil increased. Thus, this project simulated the lift and buoyancy force to generate by NACA series hydrofoils. The first objective of this project is to stimulate the value buoyancy and lift force during flow over typical NACA hydrofoils for water turbine applications. Next, this project compared the lift force produced by the NACA series hydrofoils water turbine applications. And lastly, the problems or causes that affected the lift force generated by the NACA series hydrofoils were determined. This project shows the improvement bring by NACA series hydrofoils to the value of buoyancy and lift force. This project focused on the simulation method using the software. NACA 0012 is the best NACA series hydrofoil for water turbine applications. The results were validated before being able to use them.